O Teatro radical na cena contemporânea de Fortaleza: pesquisa de linguagem e o diálogo com as práticas espetaculares tradicionais - Gilson Brandão Costa (2014)
The contemporary Brazilian theater was based on searching for performers in different regions of Brazil: men and women who aimed, through an intensive practice, an own way of thinking and creating their plays. In the state of Ceará, for example, more specifically in the end of the 1980s, the performer and playwright called Ricardo Guilherme contributed to motivate a mature reflection and also the local setting. He proposed a theater movement named Teatro Radical, which is characterized by linking concepts of the Epic Theater, thePoor Theater (by Jerzi Grotowski), the Theater Anthropology (by EugênioBarba) and also through an intensive interpretation of the Brazilian culture. The Teatro Radical was increased in the contemporary setting of Ceará causing important creations in solo and collective plays. In this respect, the interpretation of that phenomenon, based on a historical, social and esthetic approach, will be focused on the basis, the development and the movement of the theatrical practice in the city of Fortaleza, which is the capital of Ceará, focusing on the essential elements which are worked in performances: the performer, scripts, audience, the elements of traditional practices in local performances and also questions related to the myth and to identities. From an interdisciplinary approach, this thesis compares that interpretation based on the fields of history, esthetic, semiotics and anthropology. It is a proposal to understand and interpret that phenomenon through an analysis of principles, fundamentals and studies of plays which were done by the performer mentioned previously, by other performers, groups and also by experiences carried out in the acting school, the Dramatic Art Courses. The scientific method, which focuses on interpreting, constructing and developing of the Teatro Radical, is based on the study of sources that are consisted in interviews published, semi-structured interviews, speeches, photographs, videos, newspaper reports, playbills and critical thoughts.